Os Judeus Portugueses de Hamburgo A História de uma Comunidade Mercantil no Século XVII - Martins, Hugo (Premio Istituto Sangalli per la storia religiosa, 2021)
The present book investigates the social and religious history of the Portuguese-Jewish community of Hamburg during what may have been the most important period of its history - the second half of the seventeenth century. The political and economic rise of this small but influential community of New Christian bankers and merchants is analysed against the backdrop of its institutional dynamics, in an overall perspective never before conceived. The political, religious, economic, legal, charitable and disciplinary history of the community is thus explored through the analysis of the protocol books of the Portuguese Nation of Hamburg, written between 1652 and 1682. This is the intimate and fascinating journey of their everyday lives, hopes and challenges, as brought to us by their leaders.